Edukasi dan Pelatihan Strategi Customer Service Efektif Bagi Mahasiswa Perbankan Syariah - Nurzansyah, Muhammad; Khumaini, Sabik; Fadhilah, Putri; Nurmawati , Lita (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
This training aims to provide an understanding and equip students with the knowledge necessary for effective customer service. The event was held at the Faculty of Islamic Religion, attended by 80 participants. Training is conducted in three forms: providing materials, conducting strategy analysis, and engaging in role-playing. The results indicate an increase in student knowledge and competence in customer service, specifically in serving customers. It is hoped that the results of this service will contribute to the development of the Sharia Banking program, enabling it to continue playing an active role in enhancing student competence.